2007
DOI: 10.1117/12.737361
|View full text |Cite
|
Sign up to set email alerts
|

Application of nondiffracting beams to wireless optical communications

Abstract: In wireless optical communications, information is carried by coherent laser beams propagating through the free space. In realized communication channels, the standard beams created directly in the laser resonator are utilized. In recent time, an increasing attention has been focused on the so-called nondiffracting beams generated by auxiliary optical systems. In this paper, the theoretical and experimental aspects of the nondiffracting propagation of light are discussed and geometrical parameters and physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…To mitigate turbulence-induced diffraction, it has been suggested to use BG-beams. 7 However, it was found that BG-beams propagating through turbulence indeed suffer from diffraction. [8][9][10][11][12][13] This was attributed to the fact that the beam is emersed in the turbulent fluid thus preventing the beam from self-healing.…”
Section: Introductionmentioning
confidence: 99%
“…To mitigate turbulence-induced diffraction, it has been suggested to use BG-beams. 7 However, it was found that BG-beams propagating through turbulence indeed suffer from diffraction. [8][9][10][11][12][13] This was attributed to the fact that the beam is emersed in the turbulent fluid thus preventing the beam from self-healing.…”
Section: Introductionmentioning
confidence: 99%
“…Although the ideal Bessel beams with infinite transverse extent and energy cannot be produced experimentally, the quasi-Bessel beams with finite size approximation can be generated by use of holographic elements [2], an axicon [3,4,5], a Spatial Light Modulator (SLM) [6], a conical mirror [7] or a Digital Micro Mirror device (DMD) [8]. Because of their special properties, such as non-diffraction [1], selfreconstruction [9] and superluminality [10], Bessel beams have prospective applications in the fields of optical manipulation [11], the design of optics devices, imaging [12] and communication [13]. Most noteworthy, investigation results show that beams with orbital angular momentum (OAM), which are also called vortex beams, have great potential in improving the communication efficiency [14][15][16], hence the high-order Bessel beams [17][18][19], which belong to a class of OAM beams, are worthy of more attention.…”
Section: Introductionmentioning
confidence: 99%
“…Ideal nondiffracting beams [1], exact solutions of the wellknown Helmholtz equation, behave with a special nondiffracting property: they remain unchanged in free-space propagation. The special properties of nondiffracting beams, such as long focal length and self-healing [2,3], have stimulated a lot of practical applications: optical interconnections [3,4], laser machining [5,6], collimation and measurement [7], optical manipulation [8][9][10], etc. However, the characteristics possessing an infinite extent and energy make ideal nondiffracting beams physically unrealizable.…”
Section: Introductionmentioning
confidence: 99%